Change of an anode's microstructure morphology during the fuel starvation of an anode-supported solid oxide fuel cell. (8th June 2015) - Brus, Grzegorz; Miyoshi, Kota; Iwai, Hiroshi; Saito, Motohiro; Yoshida, Hideo
Abstract A RedOx cycle is one of the most dangerous factors of anode degradation due to microstructure changes. In this paper, the evolution of anode microstructure during a RedOx cycle caused by a fuel starvation process was studied using electrochemical measurements. After a power generation experiment, the anode microstructure was reconstructed using a combination of focused ion beam and scanning electron microscopy (FIB–SEM). The microstructure changes were quantified for parameters such as the tortuosity factor, tripe phase boundary density, volume fraction, connectivity and average grain size. The three dimensional microstructure reconstruction indicated that the fuel starvation condition might cause significant changes in microstructure morphology.